Neutron-induced mass shift of tin isotopes recognized using inductively coupled plasma mass spectrometry as an isotopic fingerprint on neutron reactions. (October 2021) - Rashad, A.M.; El-Said, H.; Elmaghraby, Elsayed K.
Abstract: The phenomenon of isotope shift in response to neutron irradiation was investigated. The high fission-neutron fluence of 1 . 44 × 1 0 18 cm −2 from the second Egyptian research reactor (ETRR-2) was used to induce a mass shift in a metallic tin sample. A triple-quadrupole inductively coupled plasma mass spectrometry system was used to analyze the isotope abundances in the mass range from A = 111 to A = 125 . The problem of mass bias due to kinetic fractionation on use of the inductively coupled plasma mass spectrometry system was treated by our calibrating the mass bias with a standard reference tin solution and building a response function. The response function was used to obtain absolute abundances in each mass range instead of isotope ratios. The results show that the mass shifts in the irradiated sample are dependent on the cross section of the neutron capture reaction in the tin isotopes. Highlights: Kinetic mass fractionation in an inductively coupled plasma mass spectrometry system for tin isotopes. Use of the mass spectrometric technique to follow the isotope mass shift in response to neutron-induced reactions on tin. Interplay among different neutron-induced reactions on tin isotopes regulates the final abundances.